Decision Support System for IT Equipment Procurement Prioritization Using WASPAS - Daniel Axel Bagus Putranto; Dwi Fatrianto Suyatno (Universitas Negeri Surabaya, 2026)
Determining the priority of IT equipment procurement is a critical process in supporting organizational operational effectiveness. However, procurement decision-making at PT XYZ was previously conducted manually using spreadsheet-based recording, resulting in subjective assessments, time-consuming discussions, and inconsistent prioritization outcomes. This study proposes a web-based Decision Support System utilizing the Weighted Aggregated Sum Product Assessment (WASPAS) method to support objective and data-driven IT procurement prioritization. The proposed system evaluates procurement alternatives based on five criteria: equipment importance, remaining stock, usage frequency, equipment age, and equipment price. The WASPAS method was selected because it combines the advantages of the Weighted Sum Model (WSM) and Weighted Product Model (WPM), improving ranking consistency and decision accuracy. System development was conducted using the Agile methodology to ensure iterative and adaptive development according to user requirements. The research results indicate that the developed system successfully generates automatic procurement priority rankings based on predefined criteria weights. In addition, the system provides reporting and analysis history features that support faster and more transparent decision-making processes. Black Box Testing results demonstrate that all system functionalities operate successfully according to user requirements. Therefore, the proposed system improves efficiency, accuracy, and objectivity in IT procurement decision-making processes.